Stretching Boundaries: A Comprehensive Review of Ehlers-Danlos Syndrome and its Subtypes - Sameer Sheth; Isha Oturkar; Dr. Midhun Kizhakethil (International Journal of Genetic Modifications and Recombinations, 2024)
The Ehlers-Danlos syndromes (EDS) encompass 13 inheritable disorders affecting connective tissue. These conditions arise from genetic alterations impacting the structure of connective tissue. Every variant of Ehlers-Danlos syndrome (EDS) exhibits distinct features and has specific diagnostic criteria. While certain traits such as joint hypermobility, skin hyperextensibility, and tissue fragility are common across all types of EDS. The range of clinical presentations spans from minor skin and joint looseness to severe physical impairment and potentially life-threatening vascular issues. The current Villefranche classification identifies six subtypes, many of which are associated with mutations in genes responsible for fibrillar collagens or enzymes engaged in the post-translational modification of these proteins. Classic or vascular EDS results from mutations in type V and type III collagen respectively, while mutations affecting the processing of type I collagen contribute to kyphoscoliosis, arthrochalasis, and dermatosparaxis types of EDS. The list of conditions included in the process of differential diagnosis for Ehlers-Danlos syndrome (EDS) encompasses fibromyalgia, autosomal dominant polycystic kidney disease, Marfan syndrome, hypermobility spectrum disorders, chronic fatigue syndrome, osteogenesis Imperfecta Type 1, Cutis laxa syndromes, Loey-Dietz syndrome, and depression. This review investigates Ehlers-Danlos syndrome (EDS), encompassing its diverse subtypes, genetic origins, pathophysiology, clinical manifestations, and diagnostic protocols. It sheds light on the intricate challenges faced by individuals with EDS due to the unpredictable symptomatology. The review underscores the necessity for holistic care paradigms to address the multifaceted needs of EDS patients, aiming to advance both clinical understanding and management strategies for this complex disorder.
Keywords: COL3A1; COL5A1; COL5A2; Ehlers-Danlos; Genetic disorder; Hypermobile